2014
DOI: 10.1002/rcm.6843
|View full text |Cite
|
Sign up to set email alerts
|

A framework for the extraction and interpretation of organic molecules in speleothem carbonate

Abstract: We do not aim to provide an environmental interpretation of extracted molecules, but highlight the caution necessary before doing so. We ultimately establish a framework for differentiating between organic constituents that are introduced to the speleothems during storage, handling and as artifacts of extraction, and those encapsulated in situ at the time of growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…In this study, we identified, quantified, and eliminated such contaminants using so‐called exterior/interior ( E / I ) experiments. Generally, in these experiments, hydrocarbon contaminants are identified by removing exterior rock surfaces using a diamond wafering saw (Brocks et al ., ), a micro‐ablation apparatus (Jarrett et al ., ) or an acid bath (Wynn & Brocks, ), followed by separate quantification of molecular concentrations in both the exterior (‘ E ’) and interior (‘ I ’) portions. Surficial contamination is then recognized by elevated E/I ratios for individual molecules, while indigenous hydrocarbons will commonly yield ratios of ca.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we identified, quantified, and eliminated such contaminants using so‐called exterior/interior ( E / I ) experiments. Generally, in these experiments, hydrocarbon contaminants are identified by removing exterior rock surfaces using a diamond wafering saw (Brocks et al ., ), a micro‐ablation apparatus (Jarrett et al ., ) or an acid bath (Wynn & Brocks, ), followed by separate quantification of molecular concentrations in both the exterior (‘ E ’) and interior (‘ I ’) portions. Surficial contamination is then recognized by elevated E/I ratios for individual molecules, while indigenous hydrocarbons will commonly yield ratios of ca.…”
Section: Resultsmentioning
confidence: 99%
“…We cleaned the stalagmite surfaces using 1N HCl (Wynn & Brocks, 2014) and then extracted powdered samples using a 1-mm-diameter diamond-tipped hand drill. We carried out acid digestion of the OM entrapped in the calcite using a cleaned HCl solution, prepared by repeatedly shaking HCl with dichloromethane until the fluorescence emission of the HCl was negligible (generally six times, Blyth et al, 2006).…”
Section: Stalagmite Samplesmentioning
confidence: 99%
“…Earlier finds of Archaean biomarkers are now discredited and shown to result from contamination, and it is now thought that all Archaean rocks are too thermally mature to preserve biomarkers (French et al ., ); this applies also to the vast majority of Neoproterozoic sections. It has also been established that even in thermally immature rocks, contamination is a major issue, even in young material (Wynn & Brocks, ). An example of the problem is the biomarker assemblage, indicative of a diverse microbial ecosystem including phototrophic and heterotrophic bacteria and eukaryotes, found in industrial core of presumed Sturtian‐age rocks from Brazil by Olcott et al .…”
Section: Biotic Responses and Innovationsmentioning
confidence: 99%